Smashing photoshop CS5 : 100 professional techniques - Jenkins, Sue (Smashing magazine, 2010)
EXPAND YOUR IMAGINATION Smashing Photoshop CS5 is loaded with 100 creative and innovative techniques to help jump-start your creativity and inspire you to do more with your designs and photographs